Multi-Criteria Decision Analysis in Transportation Safety Management: Prioritizing Solutions for Mitigating Tourist Bus Accidents in Indonesia - Kristina, Hana; Jaladara, Vena (BKM Public Health and Community Medicine, 2024)
Objective: This abstract aims to provide an overview of transportation safety issues in Indonesia, particularly focusing on tourist bus accidents, and propose solutions for preventing similar incidents. Content: Tourist transportation plays a crucial role in the growth of the tourism industry. However, the high incidence of tourist bus accidents in Indonesia poses a significant safety concern that requires urgent attention. Data from national news platforms recorded 43 bus accidents, 14 involving tourist buses between 2022 and 2024. Non-compliance with safety standards is a recurring issue identified as a major cause of accidents, encompassing aspects such as vehicle maintenance, driver competence, and enforcement of transportation safety regulations. A comprehensive approach is essential to address this issue. Implementing Multi-Criteria Decision Analysis (MCDA) can help identify crucial steps. Strict regulations with severe penalties for violators, comprehensive periodic vehicle inspections, standardized training for drivers and mechanics, and robust transportation safety oversight should be prioritized. Additionally, establishing bus checkpoints, maintaining bus incident records, and establishing specialized bus driver schools would significantly enhance transportation safety. Limiting driver working hours, providing incentives for compliant operators, and investing in research and development of safety technologies should not be overlooked. Intensive collaboration between the government, businesses, and the public is key to success. Only through concrete and integrated actions can we create a safe, reliable, and sustainable tourist bus transportation ecosystem, ensuring the safety and comfort of all users.